Coupled Coincidence Point Theorems in Partially Ordered Metric Spaces: Hemant Kumar Nashine, Binayak S. Choudhury, N. Metiya - Team, Support (Thai Journal of Mathematics, 2014)
In this paper we have shown that under certain assumptions an arbitrary family of mappings will have a coupled coincidence point with another function in a partially ordered metric space. The main results have several corollaries. Several existing results are improved by the main results. Two examples are given.